1999
DOI: 10.1111/j.1478-3231.1999.tb00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic stellate cell activation and liver fibrosis are associated with necroinflammatory injury and Thl‐like response in chronic hepatitis C

Abstract: HSC activation and progression of liver injury are unrelated to viral load but associated with a Th1-like response, a plausible target for the treatment of chronic hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 49 publications
6
38
0
2
Order By: Relevance
“…Nowadays, it is well established that the host immune response, which is regulated by the host genetic background, plays a prominent role in the natural history of the disease [3,8,52]. A positive correlation between a high level of pro-inflammatory cytokines secreted in response to HCV-related liver injury, and an increased necroinflammatory activity, liver fibrosis or cirrhosis was previously reported [8,10,11,53]. Cytokine production varies among individuals and is associated with certain mutations within the coding and the regulatory regions [27].…”
Section: Discussionmentioning
confidence: 89%
“…Nowadays, it is well established that the host immune response, which is regulated by the host genetic background, plays a prominent role in the natural history of the disease [3,8,52]. A positive correlation between a high level of pro-inflammatory cytokines secreted in response to HCV-related liver injury, and an increased necroinflammatory activity, liver fibrosis or cirrhosis was previously reported [8,10,11,53]. Cytokine production varies among individuals and is associated with certain mutations within the coding and the regulatory regions [27].…”
Section: Discussionmentioning
confidence: 89%
“…[20][21][22][23] Several semiquantitative scoring systems (e.g., Ishak and METAVIR fibrosis score) have been described. [24][25][26][27] All are time consuming and produce partially subjective fibrosis evaluations that are not very precise. 23 It has been shown that computerized imaging enables a precise quantification of fibrosis, and we have used this technique in a recent investigation of the effects of liver disease on cationic drug pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…70 Both factors lead to HSC activation and collagen deposition. 71,72 Moreover, HCV proteins (i.e., core protein) stimulate secretion of profibrogenic cytokines by hepatocytes and can directly induce fibrogenic actions in HSCs. Although factors such as duration of infection, gender, and alcohol consumption influence fibrosis progression, genetic factors may also play a role.…”
Section: Gene Polymorphisms Influencing Liver Fibrosis In Humansmentioning
confidence: 99%